2018
DOI: 10.1007/s13595-018-0740-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and genotypic stability in Prunus avium L. at the northern parts of species distribution range

Abstract: & Key message Large genetic variation was found in Prunus avium L. populations from the northern parts of the species distribution range. The ranking of genotypes in terms of growth was stable when tested at three trial sites within the northern parts of the species distribution range. & Context Peripheral populations especially those in the leading edge are isolated from rest of the areas in the species distribution range. This can make them less genetically diverse yet genetically distinct from the rest of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…In agreement with the earlier studies on Tilia sp. with the SSR markers (Barker, 2017;Erichsen et al, 2019;Lobo et al, 2018;Logan et al, 2015), we did not detect more than 2 alleles at all loci, confirming the diploidy of Tilia cordata. In our study, the observed heterozygosity estimates are not markedly affected by null alleles as shown by the MICROCHECKER tests and the high variation in the singe locus H o and F IS values among the populations.…”
Section: Genetic Features Of Tilia Cordata In Lithuaniasupporting
confidence: 69%
See 4 more Smart Citations
“…In agreement with the earlier studies on Tilia sp. with the SSR markers (Barker, 2017;Erichsen et al, 2019;Lobo et al, 2018;Logan et al, 2015), we did not detect more than 2 alleles at all loci, confirming the diploidy of Tilia cordata. In our study, the observed heterozygosity estimates are not markedly affected by null alleles as shown by the MICROCHECKER tests and the high variation in the singe locus H o and F IS values among the populations.…”
Section: Genetic Features Of Tilia Cordata In Lithuaniasupporting
confidence: 69%
“…with Erichsen et al (2019) study where no clear population structuring was found for Tilia cordata in Demark with the set of SSR markers. Based on the findings discussed above, this genetic structure is likely to be shaped by the balance between drift caused fragmentation and gene flow as well as local effects of urban escapes (Lobo et al, 2018). There also could be signs of adaptation to poor soils and relatively higher frost tolerance in the coldest region in Lithuaniathe northeastern highland.…”
Section: Genetic Structure Is Associated With Geography In Lithuaniamentioning
confidence: 97%
See 3 more Smart Citations